Autonomous materials discovery and manufacturing (AMDM): A review and perspectives. (2nd January 2023) - Bukkapatnam, Satish T.S.
Abstract: This article presents an overview of the emerging themes in Autonomous Materials Discovery and Manufacturing (AMDM). This interdisciplinary field is garnering a growing interest among the scientists and engineers in the materials and manufacturing domains as well as those in the Artificial Intelligence (AI) and data sciences domains, and it offers immense research potential for the industrial systems engineering (ISE) and manufacturing fields. Although there are a few reviews related to this topic, they had focused exclusively on sequential experimentation techniques, AI/machine learning applications, or materials synthesis processes. In contrast, this review treats AMDM as a cyberphysical system, comprising an intelligent software brain that incorporates various computational models and sequential experimentation strategies, and a hardware body that integrates equipment platforms for materials synthesis with measurement and testing capabilities. This review offers a balanced perspective of the software and the hardware components of an AMDM system, and discusses the current state-of-the-art and the emerging challenges at the nexus of manufacturing/materials sciences and AI/data sciences in this nascent, exciting area.